Penerapan Metode Muraja’ah Dalam Menghafal Al-Qur’an Pada Siswa di Markaz Qur’an Jakarta Timur : doi 10.58569/jies.v1i2.580 - Putri, Herlin Amanda; Uyuni , Badrah; Choli, Ifham; Adnan, Mohammad (Pascasarjana Universitas Islam Jakarta, 2023)
This article describes the method used in memorizing the Qur'an for students at Markaz Qur'an, East Jakarta. Markaz Qur'an is one of the institutions prepared for generations of Muslims to love the Qur'an and practice it by educating students to memorize the Qur'an. The desire and determination to educate students to memorize the Al-Qur'an are very big and strong. The seriousness of the Markaz Qur'an in producing generations of memorizing the Qur'an by holding tahfidz learning activities every Sunday. The memorization method used is muraja'ah. Applying this method aims to improve the quality of students' memorization of the Qur'an better and stronger on the sidelines of busyness in student activities. This study aimed to find out (1) How to apply the muraja'ah method in memorizing the Qur'an at the Qur'an Markaz, East Jakarta, (2) what support and inhibiting factors in the application of the muraja'ah method at the Qur'an Markaz, East Jakarta. This research was carried out in June 2022 using a qualitative method through data collection techniques with interviews, observation, and documentation which focused on the object and subject of the research (Ustadz/ustadzah and students). Based on the results of the study, it was shown that the application of the muraja'ah method in memorizing the Qur'an at the Markaz Qur'an is by 1) Implementation of memorizing the Al-Qur'an, 2) Methods of implementing muraja'ah in memorizing the Al-Qur'an, 3) Efforts in determining the target of memorizing Al-Qur'an mismatches and supporting and inhibiting factors in the application of the muraja'ah method at Markaz Qur'an, East Jakarta, namely supporting factors such as being given guidance before memorizing and having memorization targets.